FITOREMEDIASI MENGGUNAKAN KAYU APU (Pistia stratiotes) UNTUK MENURUNKAN KADAR COD LIMBAH CAIR TEKSTIL - Utami Sari Dewi; Slamet Santoso; Elly Proklamasiningsih (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2022)
Waste water treatment is needed to avoid the impact of pollution to the aquatic environment. Techniques for treating waste water, among others, are through phytoremediation using the help of water lettuce (Pistia stratiotes).This research aims to determine the effect of the percent covering area of water lettuce, the length of exposure time, and interaction of both in reducing levels COD, and to determine the percent of covering area, the length of exposure time, and interaction of both that is the most efficient in reducing The result of this research showed that the percent covering area, and the length of exposure time had a very significant effect of decreasing levels of COD. The most efficient percent covering area in reducing COD was in treatment of 75%. The most efficient length of exposure time in reducing COD was in treatment 9 days. The most efficient interaction of both in reducing COD levels was at treatment of 100% coverage area with exposure time of 9 days.